Recent Advances in Clinical Diagnosis and Pharmacotherapy Options of Membranous Nephropathy - Wang, Yan-Ni; Feng, Hao-Yu; Nie, Xin; Zhang, Ya-Mei; Zou, Liang; Li, Xia; Yu, Xiao-Yong; Zhao, Ying-Yong (Frontiers in Pharmacology, 2022)
Membranous nephropathy (MN) is a rare cause of nephrotic syndrome among adults, which is the leading glomerular disease that recurs after kidney transplantation. Treatment with MN remained controversial and challenging, partly owing to absence of sensitive and specific biomarkers and effective therapy for prediction and diagnosis of disease activity. MN started with the formation and deposition of circulating immune complexes on the outer area in glomerular basement membrane, leading to complement activation. The identification of autoantibodies against phospholipase A2 receptor (PLA2R) and thrombospondin type‑1 domain‑containing protein 7A (THSD7A) antigens illuminated a distinct pathophysiological rationale for MN treatments. Nowadays, detection of serum anti- PLA2R antibodies and deposited glomerular PLA2R antigen can be routinely applied to MN. Anti-PLA2R antibodies exhibited much high specificity and sensitivity. Measurement of PLA2R in immune complex deposition allows for the diagnosis of PLA2R-associated MN in patients with renal biopsies. In the review, we critically summarized newer diagnosis biomarkers including PLA2R and THSD7A tests and novel promising therapies by using traditional Chinese medicines such as Astragalus membranaceus, tripterygium wilfordii and Astragaloside IV for the treatment of MN patients. We also described unresolved questions and future challenges reveal the diagnosis and treatments of MN. These unprecedented breakthroughs were quickly translated to clinical diagnosis and management. Considerable advances of detection methods played a critical role in diagnosis and monitoring of treatment.